2013
DOI: 10.4085/1062-6050-48.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Approved Clinical Instructors: Barriers in the Implementation of Evidence-Based Practice

Abstract: Context: As evidence-based practice (EBP) becomes prevalent in athletic training education, the barriers that Approved Clinical Instructors (ACIs) experience in implementing it with students need to be understood.Objective: To investigate barriers ACIs face when implementing EBP concepts in clinical practice and in teaching EBP to professional athletic training students and to investigate the educational emphases to improve the barriers.Design: Qualitative study. Setting: Telephone interviews.Patients or Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Participants in this study specifically identified perceived barriers in the areas of knowledge related to EBP, time, accessibility of evidence, and the culture of their clinical practice environment. These results are consistent with barriers cited within athletic training [16][17][18][19][20]27 as well as other health care professions. [28][29][30][31][32][33] Although these barriers are not novel, thought and reflection should be given to if and when we can anticipate changes to these barriers, particularly now that all ATs are required to obtain 10 EBP CEUs every 2 years.…”
Section: Evidence-based Practice Resources and Barrierssupporting
confidence: 87%
See 2 more Smart Citations
“…Participants in this study specifically identified perceived barriers in the areas of knowledge related to EBP, time, accessibility of evidence, and the culture of their clinical practice environment. These results are consistent with barriers cited within athletic training [16][17][18][19][20]27 as well as other health care professions. [28][29][30][31][32][33] Although these barriers are not novel, thought and reflection should be given to if and when we can anticipate changes to these barriers, particularly now that all ATs are required to obtain 10 EBP CEUs every 2 years.…”
Section: Evidence-based Practice Resources and Barrierssupporting
confidence: 87%
“…12,14 In addition to knowledge, information has been previously disseminated regarding barriers to use and implementation of EBP. [16][17][18][19][20][21] Although valuable in content, these previous studies were conducted before the implementation of the BOC requirement regarding EBP continuing education. There is a structured process to obtaining these EBP-category CEUs through the BOC, but little information is available regarding the outcomes of EBP-approved CPE programs on ATs' knowledge and subsequent implementation of skills into practice.…”
Section: Athletic Trainers' Current Knowledge and Envisioned Use Of Fmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Both groups indicated that their own lack of knowledge was a barrier to implementing EBP with students. Ultimately, the goal of EBP is to help improve patient care through combined best evidence, clinician expertise, and the patient's goals and values.…”
Section: Confidence In Knowledgementioning
confidence: 99%
“…Developing a spirit of inquiry about the best available external evidence is essential; 7 however, time constraints on athletic trainers, lack of mentorship in evidence-based practice, and the limited availability of sources of external evidence present some major barriers for its acceptance as part of the necessary skill set for making clinical decisions. [8][9][10][11] Additionally, for many of the assessment and intervention techniques that athletic trainers use, high-quality sources of external evidence are not yet available. This unavailability actually reinforces the resistance against evidence-based practice gaining traction for inclusion in the necessary skill set.…”
mentioning
confidence: 99%